Outcome of Surgical Management of Pancreas Neoplasms in a Large Community Hospital. Issue 9 (September 2021) - Biswas, Sukanto; Udekwu, Pascal; Stiles, Anquonette; Roy, Sara
Background: Outcomes of complex pancreatic procedures have been used as an index for quality, and higher volume has been associated with improved outcomes, leading to advocacy for referral to those centers. The aim of the study was to evaluate the outcomes of pancreaticoduodenectomy (PD) at a low-volume referral center. Materials and Methods: This retrospective study included patients who had a PD within a 7-year period. Operative performance parameters and outcomes were examined. Results: Overall, there were 47 pancreatic resections, of which 38 met the inclusion criteria and were used for analyses. The overall median for blood loss, packed red blood cells units transfused, and postoperative days in hospital was as follows, respectively: 675 mL (interquartile range [IQR] = 500-900), 0 units (IQR = 0-2), 12 days (IQR = 9-18). Demographic characteristics, comorbidities, and complications align with the literature. The 30-day in-hospital mortality rate was 5%. Survival probability for those with pancreatic adenocarcinoma at 1 year was 52% and 7% for years 2 and 3. Discussion: As cases increased, significant improvement was noted in process outcomes including blood loss, blood transfusion rates, and length of stay (LOS). Survival was comparable to that in the literature, with limitation of not being adjusted for adjuvant therapy. Outcomes of complex pancreatic procedures, like PD, at a low-volume center with commitment and adequate support systems, can match those at high-volume centers.